PERILAKU IBU TENTANG MANAJEMEN NYERI TERHADAP LAMANYA PERSALINAN - Etty, Christina Roos; Damanik, Elsarika; Barus, Ernawati; Salamanang, Linda Wati (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2023)
Childbirth is the process of the birth of amniotic fluid, child, and placenta by the mother’s own power, with the age of 9 months of the calendar, 10 months of pregnancy and 37-40 weeks, through the birth canal. There are three main factors that influence labor, namely pasegge (birth canal), pessengger (fetus), and power (contractions). These three factors 90% contributed to the onset of pain during labor, most commonly caused by contractions, which occurred at the beginning of labor which increased in intensity over time. The intensity of pain in every mother in labor varies depending on the characteristics of the mother, experience, physical and psychological conditions of the mother and support during delivery. Mothers giving birth today tend to choose labor with surgery to avoid pain, one of the effects of labor pain on the mother is prolonged labor, and the baby has asphyxia. The labor pain experienced by the mother should be reduced or even eliminated if the mother is given information about how to deal with pain during labor with various relaxation techniques, positioning, mentoring, diversion and others. The purpose of this study was to determine the mother’s behavior regarding pain management during labor. This study uses an analytical survey with a cross sectional, when the research was carried out from April to May 2021, with a total sample of 30 people. The results of the chi square test p = 0.03 (P < 0.05). There is a relationship between labor pain and the length of labor. The majority of pain management behaviors during labor are still lacking. It is advisable to carry out ANC at least 4 times and if there are complaints, husbands provide physical and psychological support, for midwives to provide information through social media. Â